(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2015)
Data Mining represents a Business Intelligence (BI) methodology which provides an insight into the ’hidden’ information about its operations thus improving the process of making strategic business decisions based on a clear and understandable interpretation of existing results. Data mining can help to resolve banking problems by finding some regularity, causality and correlation to business information which are not visible at first sight because they are hidden in large amounts of data. The goal of this paper is to present a case study of usage of operations research methods in knowledge discovery from databases in the banking industry. Neural network method was used within the software package Alyuda. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.